2020
DOI: 10.3390/biom10071054
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition of Cumin Seeds, and Biorefining Study

Abstract: A new biorefinery approach has been developed in the present study, and applied on cumin (Cuminum cyminum) seeds as a potential source of phytochemicals of interest. Cumin is a popular spice used widely for its distinctive aroma. It is a rich reserve of both vegetable and essential oils. The biorefinery approach here focused on the evaluation of the influence of four different geographical origins (i.e., Lebanon, France, Algeria and Syria) on oil yield and quality in cumin seed, and on the valorization of rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 73 publications
4
43
0
1
Order By: Relevance
“…Other authors’ findings have also shown a high proportion of linoleic, oleic, and palmitic acids. A large proportion of petroselinic acid has also been detected [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors’ findings have also shown a high proportion of linoleic, oleic, and palmitic acids. A large proportion of petroselinic acid has also been detected [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the addition of BCS and BCW, which also had a low fat content, could have a positive effect on the volume of bread. According to other studies, oil additives to bread dough act as surfactants that can bind to starch granules, thereby stabilizing and strengthening the dough, which could consequently increase the volume of bread [ 23 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cumin seed is valued for its aroma, which is due to the presence of cuminaldehyde, cuminic alcohol, p-cymene, o-cymene, γ-terpinene, α-terpinene, p-menthadienol, and β-pinene as some of its chief components [80,81]. High levels of a rare, monounsaturated, omega-12 fatty acid, petroselinic fatty acid (C18:1), are also present in cumin [82].…”
Section: Cuminum Cyminummentioning
confidence: 99%
“…Cumin has beneficial effects in curing tastelessness, poor digestion, cardiovascular disease, swellings, vomiting, and chronic fever in humans [1,2]. Cumin seeds have nutritional quality i.e., 100 g of seed include energy 370 kcal, dietary fiber 10.5 g, proteins, 22.27 g fat, 44.24 g carbohydrates, and 10.5 g fiber, as well as vitamins and minerals [3]. Several studies have revealed that cumin seeds can also increase vitamin C intake [4,5].…”
Section: Introductionmentioning
confidence: 99%